2022
DOI: 10.1007/s00204-022-03332-z
|View full text |Cite
|
Sign up to set email alerts
|

Going deeper into the toxicokinetics of synthetic cannabinoids: in vitro contribution of human carboxylesterases

Abstract: Synthetic cannabinoids (SC) are new psychoactive substances known to cause intoxications and fatalities. One reason may be the limited data available concerning the toxicokinetics of SC, but toxicity mechanisms are insufficiently understood so far. Human carboxylesterases (hCES) are widely known to play a crucial role in the catalytic hydrolysis of drugs (of abuse). The aim of this study was to investigate the in vitro contribution of hCES to the metabolism of the 13 SC 3,5-AB-5F-FUPPYCA, AB-5F-P7AICA, A-CHMIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Uchiyama et al and McLaughlin et al analyzed 3,5-AB-CHMFUPPYCA, the latter identifying the substance in a sample that was incorrectly advertised as 5F-5,3-AB-PFUPPYCA, while also showing the synthesis and characterization of the regioisomer 5,3-AB-CHMFUPPYCA [29,33] . Furthermore, metabolism of these compounds was investigated by Franz et al [34] , who also looked at their thermal stability, and more recently by Wagmann et al [35] .…”
Section: Introductionmentioning
confidence: 99%
“…Uchiyama et al and McLaughlin et al analyzed 3,5-AB-CHMFUPPYCA, the latter identifying the substance in a sample that was incorrectly advertised as 5F-5,3-AB-PFUPPYCA, while also showing the synthesis and characterization of the regioisomer 5,3-AB-CHMFUPPYCA [29,33] . Furthermore, metabolism of these compounds was investigated by Franz et al [34] , who also looked at their thermal stability, and more recently by Wagmann et al [35] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that the hydrolysis of the related SCRAs QMPSB, 2F‐QMPSB, BB‐22, PB‐22, and 5F‐PB‐22, which also have an 8‐hydroxyquinoline ester head group, was mainly catalyzed by hCES1 as well 12,13,25 . Furthermore, a study on SCRAs containing a methyl ester showed that mostly hCES1 catalyzed the hydrolysis 26 …”
Section: Resultsmentioning
confidence: 99%
“…12,13,25 Furthermore, a study on SCRAs containing a methyl ester showed that mostly hCES1 catalyzed the hydrolysis. 26 Incubations with pHLM and pHLS9 revealed a faster increase in the hydrolysis product than the control incubations indicating enzymatic ester hydrolysis as well. In both incubations, QMiPSB was almost completely degraded after 8 or 14 min, so no further ester hydrolysis was possible.…”
Section: Carboxylesterases Activity Screening Of Qmipsbmentioning
confidence: 88%